Exploring Buddhism Values at Sari Temple: An Investigation in a Buddhist Tourism Destination - Shadikah, Arina Afiyati (Indonesian Values and Character Education Journal, 2023)
Religious tourism has now become one of the favorite destinations for tourists. However, there are still many temples that are not widely known by tourists. Even though many temples, such as Sari Temple, have a certain charm, such as the shape of the temple which is like a house complete with doors and windows. However, there is still minimal information regarding the history and meaning of the temple reliefs. This research was carried out at the Sari temple which is located in Uang Istimewa Yogyakarta. This research aims to analyze the Buddhist values at Sari Temple based on the history of this temple. This research uses a qualitative research design where the research object is Sari Temple itself. There are three techniques used to collect data, namely interviews, literature study, and documentation. The data collected was then analyzed qualitatively through four stages, namely data collection, data reduction, data presentation, and verification or drawing conclusions. The results of the research show that there are three Buddhist values that can be found based on the history of Sari temple, namely samma sankappa (right thoughts) , samma kamanta (right action) and samma vaca (right speech). Each of these Buddhist values has moral values in it.